POLITICAL DISCRIMINATION TOWARD WOMAN IN THE PRINCESS DIARIES 2 : ROYAL ENGAGEMENT MOVIE : AS A FEMINISM STUDY - Vera Putri Ramadhanty; Yulistiyanti Yulistiyanti (Universitas Stikubank (UNISBANK) Semarang, 2021)
ABSTRACT The study analyze how the political discrimination happen in Royal Family and how the main character response from her action to get the throne. This study used Princess Diaries 2: Royal Engagement movie as the data. This study used qualitative method. In collecting the data the researcher watched the movie and read the script. The theory used in this study is Kate Millet: Sexual Politics. Millet’s theory provides that sex is politic. It means the relationship of women in society with men is a political relationship, a relationship that is based on the structure of power, namely a group of people which is controlled and dominated by other humans. The findings show that the main character gets political discrimination from The Royal Parliaments and there is an ambition from a third part who wants to overthrow position in the first place in the throne. The researcher has found the action of female characters to gain the throne in this movie. There are some activities that Mia should learn to be a queen. Mia learns to practice all outdoor activities with the traditions of the Genovian Royal Family. Starting from learning archery to prepare for the night of ceremony when she later took the throne, and horse riding as a review Royal Guard. The end of the movie, Mia asking all member of The Royal Parliaments to change that law who purpose a woman to get married first before she gets the throne. Keywords: feminism, sexual politic, movie, political discrimination.